Pengaruh Harga dan Promosi Terhadap Kepuasan Pasien dengan Pelayanan Sebagai Variabel Intervening Pada RS Bina Kasih Pekanbaru - Christ Windreis (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The hospital is one of the places to meet the needs and expectations of patients in solving their health problems, one of which can be fulfilled by providing satisfaction to patients. Patients can feel satisfaction can be determined by the fact that the services provided can meet the needs and expectations of patients. , by using the patient's view of the service received (satisfactory or disappointing, also including the length of service time). Services that are not in accordance with expectations, patient needs and lack of quality will form a dissatisfaction with the patient. There are several factors that can occur in terms of satisfaction of a hospital, one of which is the cost or the price of the costs incurred. The results of the research on the price effect on satisfaction at the hospital. RS. Bina Kasih Pekanbaru. Promotion has an effect on satisfaction at the hospital. RS. Bina Kasih Pekanbaru. Service moderates the effect of price on satisfaction at the hospital. RS. Bina Kasih Pekanbaru.and service moderated the effect of promotion on satisfaction at the hospital. RS. Bina Kasih Pekanbaru